Erratum to: Search for non-relativistic magnetic monopoles with IceCube (The European Physical Journal C, (2014), 74, 7, (2938), 10.1140/epjc/s10052-014-2938-8) - Aartsen, M. G.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Altmann, D.; Arguelles, C.; Arlen, T. C.; Auffenberg, J.; Bai, X.; Baker, M.; et al. (European Physical Journal C: Particles and Fields, 2019)
In the analyses, published in Ref. [1], the exclusion limits are calculated in dependence of the mean free path of the magnetic monopole - nucleon catalysis interaction.
CRIS-Team Scopus Importer:2019-05-02